Case Study of Energy Saving in an Industrial Setup by Replacing Conventional Bulbs with LED Lights - Khanam, S.; Hanif, A. (The Nucleus, 2014)
Lighting accounts for roughly one-fifth of global electricity consumption. The demand for energy is increasing day by day with increase in population, change in life style, and change in technology. This growing demand led to energy crisis which is the biggest threat for economic stability for developing countries like Pakistan. This crisis has badly affected the everyday life and industry. To overcome energy shortfall one solution is to focus on energy conservation. Significant energy savings can be achieved by reducing energy consumption by artificial lighting which has potential of energy saving by using efficient lighting technologies such as Light Emitting Diodes (LEDs). A case study is carried out for an industrial setup to compare the performance, suitability and financial effects of conventional bulbs and LED lights in an industrial setup. A new lighting scheme has been designed by using DIALux 4.11 simulation software based on international standards of Illuminating Engineering Society of North America (IESNA).The conventional bulbs on the shop floor has been replaced with LED lights as per software design. After hardware installation it is revealed that by adopting this lighting scheme there is 45% of energy savings and user satisfaction with financial savings of Rs. 912,711 per year having 3.78 years pay back period that justifies use of LEDs as per proposed lightning design for general lighting applications.